Information orientation of a public organisation : a qualitative case study of the information orientation in the Department of International Relations and Cooperation - Tshirado, Nkhumbudzeni Maskew (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.